Efektifitas Model Pembelajaran Quantum Teaching and Learning Terhadap Motivasi Belajar PAI Siswa Kelas IV - Haerudin; Anggy Giri Prawiyogi (Jurnal Sekolah Dasar, 2019)
In this study aims to determine the effect of learning motivation on PAI students in grade IV who have implemented the Quantum Teaching and Learning learning model with the motivation to learn PAI in fourth grade students who apply Conventional learning models. The method used in this study is a quasi-experimental method, the data collection technique uses a questionnaire, and to determine the control and experimental classes used the pretest-posttest control group design, which class is of low value and will be used as the experimental and class high grades will be used as a control class. The object of his research was fourth grade students of SDN Tegal Sawah I, which numbered 40 people, divided into 2 classes, experimental class 20 people and classes. Control 20 people. Based on the results of research and data analysis, the average experimental class pretest was 49.4 and the control class was 48.25. After being given treatment and posttesting that the results of the experimental class were 68.1 higher than the control class average value of 54.75. Calculation of hypotheses using the t-test is a paired sample T test and obtained at a significant level of 0.05 shows that the probability value (significance) is 0.00. because of the significance value, then Ho is rejected. This proves that the use of the Quantum Teaching and Learning learning model influences the learning motivation of PAI students in fourth grade SDN Tegalsawah I.